Овоот хурлын хотгорын нүүрсжилт - М. Очирбат; Н. Болдбаяр; Н. Намсрай (Geological Issues, 2023)
In this paper, we report die documentation of coal seam structure as well as the sedimentological observation of Ovoot Khural depression based on data, compiled during the extensive drilling programs for coal exploration. The depression lies in the Ovoot Khural coal district of Southgobi coal-bearing basin according to the classification of Mongolian coal-bearing basins. The Ovoot Khural depression is 3-6 km wide and over 100 km long, and hosts 16 coal deposits and occurrences. The thickness of coal seams range from 5 m to 150 m. At the east and west part of the depression, number of coal seam increases but thickness of coal seam decreases, in other side it is opposite increasing thickness of coal seam but decreases the number of seam at die central part of the depression. Coal seams are hosted in non-marine sedimentary sequences, of which exact age is matter of controversy. Previously, it was thought to be Upper Permian, but in 1990s, the age was postulated as Triassic. However, in late 2000s, the age was revised to Lower-Middle Jurassic, based on flant remains and palynomorphs collected from coal samples from open pit and drill cores. Now, this age is generally accepted.